INVENTARISASI BEST PRACTICES PENGELOLAAN PENDIDIKAN DI TINGKAT SEKOLAH (SMP NEGERI I TAMBUN SELATAN) - Bedjo Sujanto (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
The objective of this research is to describe stocktaking of best practices in educational management at school level. The research is conducted at Goverment Junior High School I (SMP Negeri) in Southern Tambun in the school year of 2004/2005. The most important finding in the government junior high school is that the school is able to empower the role of parents and society optimally particularly in providing fund to gain the best achievement. The success of education provision by empowering the role of parent and society optimally can be predicted if there is no wrong decision taken by the leaders. The decision is effective if all human factors as supervisors of all activities get strategic positions. To appoint human resources in the strategic position will produce strategic programs which will give a larger opportunity for success. The research finding can have implication on the efforts in sustaining the trust of parents and society around the school, so that the schools can have better quality at national level.